Simultaneous degradation of cephalexin, ciprofloxacin, and clarithromycin from medical laboratory wastewater by electro-Fenton process - Basturk, Irfan; Varank, Gamze; Murat-Hocaoglu, Selda; Yazici-Guvenc, Senem; Can-Guven, Emine; Oktem-Olgun, Elmas Eva; Canli, Oltan (ELSEVIER SCI LTD, 2021)
This study aimed to investigate antibiotic removal from medical laboratory wastewater by the electro-Fenton (EF) process. The central composite design was applied as the statistical and mathematical method to determine the optimum process conditions. The system responses were Cephalexin, Ciprofloxacin, and Clarithromycin removal while initial pH, current, reaction time, and H2O2/COD ratio were independent variables. The correlation coefficients of all responses were above 80 % and they were sufficient and acceptable. Optimum operation conditions were pH 2.99, current 3.93 A, reaction time 35.3 min, and H2O2/COD ratio 1.09. The removal efficiencies obtained in validation experiments conducted at optimum conditions were 99.12 %, 98.65 %, and 99.38 % for Cephalexin, Ciprofloxacin, and Clarithromycin, respectively. As a result, it was determined that the response surface methodology is a suitable method for the optimization and design of electro-Fenton process parameters and the EF process is an efficient technology for removing antibiotics from medical laboratory wastewater.
Keywords: Advanced oxidation; Central composite design; Cephalexin; Ciprofloxacin; Clarithromycin; Engineering